An automated functional testing approach for virtual reality applications. (12th October 2018) - Corrêa Souza, Alinne C.; Nunes, Fátima L. S.; Delamaro, Márcio E.
Summary: Software testing is regarded as an important method for fault revealing. Despite this advantage, it has been poorly used within the scope of virtual reality (VR) applications because they are highly complex and have peculiar features. Most testing performed of this VR applications are usability, which is conducted manually and only at final of the development process. Although some works try to propose criteria for this domain, there are no approaches that automatize the generation of test data from requirements specification in the VR domain. This paper proposes an approach called virtual reality—requirements specification and testing (VR‐ReST) to assist the requirements specification through a semiformal language and uses structural test criteria to generate test requirements and test data automatically for VR applications using scene graph concepts. The paper also examines the empirical results concerning the cost‐effectiveness of the approach for three different VR applications through two experiments. Mutation testing was used to evaluate effectiveness. We found that the approach achieved a high mutation score outperforming random testing, by 20%, on average. Our results also demonstrate that the approach is promising since it assists in writing and validating the requirements, as well as in reducing the risks of requirement specification by adopting a semiformal language. Abstract : We introduce VR‐ReST, an approach to assist requirements specification through a semi‐formal language. Our approach uses structural test criteria to generate test requirements, and, from those requirements, supports the generation of test data for Virtual Reality applications. Experimental results show that VR‐ReST helps in writing and validating the requirements and produces effective test data able to detect different faults both before and during the development of the Virtual Reality applications.